La Chapelle : un lieu de mémoire pour la diaspora tamoule ? - Anthony Goreau-Ponceaud (Conserveries Mémorielles)
From the analysis of an ethnic district - "la Chapelle", located between the 10th and 18th arrondissements of Paris - I want to highlight the processes of semiotisation and appropriation of the space used by Tamil migrants from Northern Sri Lanka, while wondering about the symbolic apparatus used by these migrants to make this space familiar. By an approach, combining sociality, historicity and spatiality, this contribution aims to restore the steps of the structuration of this particular form of collective existence that is the Diaspora. I will focus my analysis on the stories of a new process of territorialization, on the reshaping of a collective language, and on new social frameworks of memory.